Review Article: Potential of Natural Extracts on the Inhibition Zone of Acne vulgaris – Causing Bacteria - Haryanto, Wahyu; Hidayati, Agriana Rosmalina (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2026)
Acne vulgaris is a chronic inflammatory skin condition in which bacterial colonization plays a central role in lesion development. Growing concern regarding antibiotic resistance have encouraged the exploration of natural extracts as alternative antibacterial agents. This narrative literature review aims to analyze the zone profiles of natural extracts evaluated using diffusion assays against acne-associated bacteria, including Cutibacterium acnes, Staphylococcus aureus, and Staphylococcus epidermidis, and to identify factors controbuting the variability of antibacterial activity. A total of 22 primary studies published between 2015 and 2025 were retrieved from Google Scholar, PubMed, and Garuda and analyzed descriptively. The reviewed studies reported inhibition zone diameters ranging from approximately 10 to 25 mm, indicating varying degrees of antibacterial activity. Differences in inhibition zones were influenced by extract concentration, extraction solvent, and diffusion method. Overall, natural extract demonstrated promising antibacterial potential in preliminary in vitro screening assays; however, methodological variations should be carefully considered when interpreting inhibition zone results.